ChemInform Abstract: Rapid Assembly of Polycyclic Structures via Sigmatropic Rearrangement of S‐Propargyl Xanthates. Issue 17 (4th April 2013) - Harrington, Ryan M.; Wright, David; Zard, Samir Z.
Abstract Propargyl xanthates undergo rearrangement to afford intermediary bis(alkylidene)dithiolanones which are trapped by Diels‐Alder cycloaddition to yield dithiolones, representing three new carbocycle types such as (II), (VIII), and (X).